Pengaruh Perbedaan Dosis Biolacto pada Pakan terhadap Pertumbuhan Berat Mutlak Udang Vaname (Litopenaeus Vannamei) Doc 50 Hari - Afan Auriel Ramlanis; Sumaryam Sumaryam; Achmad Kusyairi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
The purpose of this study was to determine the effect of different doses of Lactobacillus in feed on the absolute weight growth of whiteleg shrimp (Litopenaeus Vannamei) doc 50 days. The study was conducted for 30 days at CV. Sukses Indah Prima. The research method used was an experimental method with a completely randomized design (CRD) using 4 treatments and 6 replications. The treatments were as follows: treatment A. without the addition of biolacto probiotics; treatment B. addition of biolacto probiotics 50 ml / kg of feed; treatment C addition of biolacto dose 70 ml / kg of feed; treatment D addition of biolacto probiotics 90 ml / kg of feed. Absolute weight growth data were analyzed using one way ANOVA 5%. The results of the ANOVA test showed that the difference in biolacto doses in feed had a very significant effect on the absolute weight growth of whiteleg shrimp (Litopenaeus Vannamei) doc 50 days and B) Treatment D biolacto dose 90 ml / kg of feed is the optimal dose, providing absolute weight growth of vannamei shrimp with an average of 9.37 grams.